MEDICAL SUPERVISION IN SPECIALIZED CENTER AND THE QUALITY OF LIPID-LOWERING THERAPY IN PATIENTS WITH CARDIOVASCULAR DISEASES (ACCORDING TO THE PROFIL REGISTER) - S. Yu. Martsevich; O. V. Gaysenok; S. G. Tripkosh; A. V. Zagrebelnyy; Yu. V. Lukina (Столичная издательская компания, 2015)
Aim. To assess the quality of lipid-lowering therapy in high risk patients with cardiovascular diseases during medical supervision in specialized center.Material and methods. The data of the PROFIL register are used. All patients having cardiovascular diseases, high cardiovascular risk, and seeking medical attention in specialized medical center were enrolled into this register. Patients (n=274) were split into groups: control group (n=82, patients who have applied for the first time for medical care), the main subgroup A (n=167; patients observed last 2 years), and the main subgroup B (n=25; patients observed more than 2 years).Results. The total cholesterol blood level was significantly lower in the main group compared to the control (p<0.05). Statins were constantly taken by 34% of patients in the control group, 71.6% - in subgroup A, and 61% - in subgroup B (p<0.05).Conclusion. Medical supervision in specialized medical center leads to better blood lipid control and patient compliance to statin therapy.